Pengaruh Environmental, Social, Governance (ESG), Green Accounting, dan Growth Opportunity Terhadap Nilai Perusahaan - Tabita Safa Callula Pangestu; Khomsiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of Environmental, Social, Governance (ESG), Green Accounting, and Growth Opportunity on the firm value of energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. This research employs a quantitative method using secondary data from annual reports, financial statements, and sustainability reports. The population includes all energy sector companies listed on the Indonesia Stock Exchange during the study period, with samples selected using the purposive sampling method. The analysis technique applied in this study is multiple linear regression analysis. The results indicate that Green Accounting has a significant positive effect on firm value, whereas ESG and Growth Opportunity do not significantly affect firm value. These findings reveal the importance of implementing Green Accounting as a sustainability strategy to enhance investor confidence and corporate competitiveness.